Trends in hydrologic time series and the climate change: some of the portuguese experience - Santos, João Filipe; Portela, Maria Manuela; Quintela, António de Carvalho; Vaz, Cristiana (My University, 2009)
Nowadays it is often mentioned that the Earth is already suffering the climate change effects: it is no longer a matter of future climate scenarios but instead of frequent abnormal climate occurrences. If changes are already happening then they should be embedded in some of the hydrologic time series, with emphasis to those series more closely related to the weather, as the precipitation series. In the previous scope a research is been carried since the last years aiming at detecting trends in Portuguese hydrologic time series by means of statistical and simulation approaches and at relating such trends with the climate change. The results from the trend analysis applied to precipitation series in more than one hundred rain gages showed that some months exhibit a upwards trend while other months denote a downward trend or even no trend at all. Changes in the precipitation monthly pattern may also seam to occur, those changes compensating each others and resulting in unchanged annual precipitations. In general terms, the study showed that, except for March, most of the trends are not significant from a statistical point of view, being explained by the natural temporal variability of the precipitation. Along with the previous analysis the performance of the several hypothetical artificial reservoirs was also analysed. In fact, in Portugal most of the water supplies are ensured by artificial reservoirs created by dams, a significant part of these infrastructures having been built in the early fifties and sixties. The trends denoted by the hydrologic series may suggest that, comparatively to the design criteria, the inflows to those reservoirs may also have changed. So, a question arises: are the reservoirs still able to ensure the volumes adopted as design criteria with the reliability/guaranty required by each type of water utilization? This question is especially pertinent when reservoirs for irrigation purposes are under consideration as both the crop demand and the water availability may be influenced by the trends exhibit by the hydrologic series. To answer this question, the performance of ten hypothetical irrigation reservoirs was analyzed, by means of computational simulation techniques. The results achieved show that most of the case studies denote loss of reliability as more storage capacity should be presently required. However the increases of the storage capacity were almost negligible.
Comunicação apresentada no EcoHCC'09 - International Conference on Ecohydrology and Climate Change, Tomar (Portugal)
Keywords: Performance of water supply systems; Trend analysis; Hydroclimatological variables